Can Virtual Reality Increases Students Interest in Computational Chemistry Course? A Review (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
Computational chemistry is one of the branches in chemistry that implies the finding of theoretical chemistry into efficient computer programming to monitor, calculate and examine the properties of molecules and solids, adopting these programs to real chemical problems. Intersection between virtual reality (VR) and computational chemistry would bring the strength and improve the weakness of the system for better chemistry field discovery among scholars that level up the educational development. Thus, introduction of VR as an educational medium will eventually add another new technical skill for good purpose mainly for processing data and information. This paper reviews the role of VR as a teaching device in computational chemistry courses. The innovation in teaching and learning helps students to collect more reliable and quality data on the chemical analysis that is not available from the experimental works. This will provide source and bridge for the students to easily collect and analyse data in comprehensive understanding especially deep explanation at atomic level. This teaching strategy also stimulate and attract the interest of the students to be more joyful and native in learning.